2018
DOI: 10.1002/fsn3.662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of postharvest treatments with chitosan and putrescine to maintain quality and extend shelf‐life of two banana cultivars

Abstract: Chitosan (1.0% and 2.0%) and putrescine (1.0 and 2.0 mmol/L) treatments were used to investigate the effects of these compounds on the postharvest quality and shelf‐life of two banana cultivars, “Native” and “Cavendish.” Fruits were stored at 15 ± 2°C and a relative humidity of 85%–90% during a 20‐day period. In the controls, increases in weight loss, microbial population, total soluble solids, and ethylene production and decreases in firmness, ascorbic acid contents, and fruit lightness occurred gradually dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 41 publications
0
24
0
1
Order By: Relevance
“…Chitosan-ascorbic acid coatings inhibited the browning of apple pieces, and browning inhibition was enhanced by increasing the ascorbic acid and chitosan ratio in the solution. These results were also supported by the studies on the beneficial side of chitosan on browning [41][42][43]. In addition, antibrowning agents such as ascorbic acid and citric acid suppress the polyphenol oxidase activity working as reducing agents [44].…”
Section: Colormentioning
confidence: 61%
“…Chitosan-ascorbic acid coatings inhibited the browning of apple pieces, and browning inhibition was enhanced by increasing the ascorbic acid and chitosan ratio in the solution. These results were also supported by the studies on the beneficial side of chitosan on browning [41][42][43]. In addition, antibrowning agents such as ascorbic acid and citric acid suppress the polyphenol oxidase activity working as reducing agents [44].…”
Section: Colormentioning
confidence: 61%
“…El-Garhy et al [ 22 ] demonstrated that the pre-harvest spraying of bean plants with potassium thiosulfate decreased the pod rots caused by Botrytis cinerea and Sclerotinia sclerotiorum . Additionally, chitosan significantly decreased the microbial population on banana fruits during storage [ 61 ]. In the case of 15 days of cold storage, spraying tomato plants six times with chitosan was significantly more effective in reducing black mold infection in tomato fruits inoculated with A. alternata compared to three sprays.…”
Section: Resultsmentioning
confidence: 99%
“…NF technology is very innovative and there are very few reports on their applications to fruit trees. Chitosan (C 6 H 11 O 4 N n ) is a polymer that is found in seafood wastes with many potentials for agricultural application such as increasing crop production and the quality of agricultural products . Chitosan NPs, when prepared by a nano spray dryer, and applied at 10 mg L −1 increased chlorophyll and photosynthesis rate, nutrient absorption, and seedling growth in coffee plants compared to the control .…”
Section: Nps Act As a Stimulatory Growth Factor In Fruit Treesmentioning
confidence: 99%